Utilization of Meso-scale Weather Models in Urban Development Policy and Planning: A Review - Latue, Philia Christi; Manakane, Susan E; Rakuasa, Heinrich (Yayasan Sinergi Kawula Muda, 2023)
The policy in dividing the KBI and KTI regions is intended to avoid development imbalances that occur in Indonesia. Development in Eastern Indonesia is considered disproportionate and only focused on the Western Region. But now the priority of regional development will be focused on Eastern Indonesia. As a large city in North Sulawesi that is included in Eastern Indonesia, Manado has a strategic location as an investment gateway to economic growth in Eastern Indonesia, this is the background for the development plan of Mapanget sub-district which is included in the Manado City area to become a new city center. This research aims to assess the feasibility of the Mapanget area as the object of this strategic project. The method used was a literature study in combination with the availability of secondary data obtained from research, records and provisions related to the analysis of new city development. Based on the results of the various elements of new city development such as residential areas, health and education facilities, trade, services and industry, and population accessibility have experienced large growth in the period (2007-2019) or in the last twelve years. In terms of development planning, there are also complete guidelines that are based on an in-depth study of various aspects, so it can be concluded that Mapanget Sub-district is strategic enough for the development of a New City in Eastern Indonesia.